An analytical study on identification and system productivity of rice based integrated farming system in Jharkhand - Kumari, Shweta; Jha, Basant Kumar; Kumar, Anup; Kumari, Neetu; Kumar, Avinash; Mishra, Shivam (ORYZA-An International Journal of Rice, 2025)
Rice-based integrated farming system (IFS) offers a sustainable approach to enhancing agricultural productivity, income diversification, and ecological balance, particularly in resource-constrained regions like Jharkhand, India. This study investigates the adoption of rice-based IFS among 90 farmers across three agro-climatic zones of Jharkhand and assesses their productivity through rice grain equivalent yield (RGEY). Data were collected through personal interviews and field surveys, identifying 15 distinct IFS combinations involving cereal crops, livestock, poultry, and horticultural crops.  Results indicated that the "Rice+dairy+goatry+poultry+vegetable" system was the most adopted (30%), followed by "Rice-wheat+dairy+goatry+poultry+vegetable" (14.40%). Rice+maize+dairy+ goatry+poultry +vegetable system achieved the maximum rice grain equivalent yield (RGEY) with the productivity of 51,721 q/ha. Systems incorporating a broader range of components exhibited higher productivity, emphasizing the importance of diversification in enhancing resource use efficiency. The study emphasizes the need for targeted interventions, including localized research, capacity building, and support systems to promote wider adoption of rice-based IFS which has high potential to improve productivity and sustainability in rice-dominated agricultural systems.